Aerobic Exercise Terhadap Peningkatan Endurance Pada Pasien Penyakit Jantung Koroner Dengan Pemeriksaan 6MWT : Studi Kasus - Fuadi, Dela Fariha; Saputra, Andrew Wijaya; Dzatikhulwani, Nabilla Nur Awaliah (Jurnal Fisioterapi Terapan Indonesia, 2023)
Background: Coronary heart disease (CHD) is a condition in which the heart's blood vessels (coronary arteries) are blocked by fat deposits. Based on data from Riskesdas (2018) it is revealed that cases of heart and blood vessel disease in Indonesia are increasing every year, increasing the mortality rate. This is due to the presence of risk factors that support the emergence of coronary heart disease. Objective: The aim of this paper is to evaluate the evaluation of aerobic exercise to increase endurance in patients with coronary heart disease by examining 6MWT. Method: This research is in the form of a case study with direct data collection methods. The population in this study were female CHD patients who were treated at a hospital with the age of 65 years. Data collection and intervention were carried out on 30 December 2021-06 May 2022. Results: This report was taken from the case of a patient with the initials Mrs. S with a diagnosis of Coronary Heart Disease aged 65 years with the main complaint of fatigue when walking, shortness of breath. After being given physiotherapy interventions in the form of breathing exercises, strengthening exercises and endurance exercises can reduce the degree of shortness of breath from 3 to 1 and can increase endurance from the METs scale of 1.6 to 3.35. Conclusion: Endurance exercise, strengthening exercises and breathing exercises can reduce the degree of shortness of breath and increase endurance in patients with Coronary Heart Disease.